Rolled wheel center hubs for mainline diesel-electric locomotives 2ТE10, 2ТE116 - G. I. Bryunchukov; A. V. Sukhov; D. E. Kerentsev; A. S. Razumov (Вестник Научно-исследовательского института железнодорожного транспорта)
Given below are results of development and implementation of a pilot batch of rolled wheel center hubs made of steel grade ‘S’ at the JSC VMZ Iron and Steel Works designed to replace stock-produced cast wheel center hubs in mainline diesel-electric locomotives 2ТE10, 2ТE116. Flow line production of rolled wheel center hubs includes a mill for rolling center disk-type wheels where wheel center hubs are made of medium carbon/low-alloy steel with further heat treatment (namely normalizing and stress relieving). The rolled wheel center hubs have an optimized low-stress configuration and are supplied with all its surfaces machined. Within the standard routine preceding mass production, the rolled centers were tested in a laboratory where a full package of mechanical properties were analyzed, were tested on a rig for crack resistance (or fracture toughness), also a pilot lot was tested on the Experimental Loop (JSC VNIIZhT) and were tested in revenue operations performed by Severnaya Railway Operator where they were installed in the wheels of diesel-electric locomotives. Test results have shown that the new rolled wheel center hubs made of steel grade ‘S’ demonstrated improved reliability in revenue operations due to higher steel quality and higher parameters of strength, fatigue life and fracture toughness. Additionally, the use of a new steel grade, optimized center hub design, and a new manufacturing technology - rolling instead of casting - have resulted in a substantial cuts of wheel centers production costs and a 10 % decrease of assembled weight. Due to positive results of tests in revenue operations the company JSC VMZ has held the acceptance test procedure related to rolled wheel center hubs made of steel grade ‘S’ and registered a permit to manufacture as much as a preproduction batch. Results of this work have been taken as a basis for the new standard GOST R 55498 - 2013 ‘Rolled wheel center hubs for the railway rolling stock. Technical specifications’.